Bioremediation Experiment Using Hydrocarbon Degrading Bacteria - Susilawati, Rita (Pusat Survei Geologi, 2019)
A laboratory experiment was set up to demonstrate the capability of microbe to remediate petroleum hydrocarbon contaminated beach sand. Oil contaminated soil was used as a source of inoculum for hydrocarbon degrading bacteria (HDB) while oil contaminated beach sand was used as remediation object. The growth of HDB in the inocula was enriched and stimulated through the addition of nutrient in the form of vitamin and mineral as well the addition of oil waste as a source of carbon. Experiment took place in the course of approximately five weeks. Microscopic observation clearly showed the interaction between microbe and oil contaminant both in enrichment and bioremediation samples. The result of the experiment also suggests that approximately 25% of the petroleum hydrocarbon mass in the contaminated beach sand was biodegraded over the course of one month. Overall, the results of this experiment suggest the potential of bioremediation method to treat petroleum hydrocarbon polluted environment.Keywords: bacteria, bioremediation, hydrocarbon DOI: 10.33332/jgsm.2019.v20.1.1-7